Correlation Between Brixia Score Imaging and Clinical Laboratory Results In Severe-Critical Covid-19 Patients Receiving Standard Therapy Compared To Tocilizumab - Aulia Fitriani; Frederica Mardiana Wahyuni; Bambang Satoto; Thomas Handoyo; Antonius Gunawan Santoso; Christina Hari Nawangsih; Nurdopo Baskoro (Medica Hospitalia : Journal of Clinical Medicine, 2024)
Background. Coronavirus infection disease 19 (COVID-19) is a global health issue. Brixia score and inflammatory markers can assess COVID-19 severity. Severe-critical phase becomes the main concern of clinicians in the management of COVID-19 to reduce mortality. Standard therapy for moderate to severe COVID-19 is convalescent plasma which functions as an antiviral and immunomodulator, while tocilizumab is an IL-6 antagonist which underlies the occurrence of cytokine storms in severe-critical COVID-19. Aims. To examine the correlation between the Brixia score and clinical laboratory results in patients with severe-critical degree of Covid-19 who received both standard therapy and tocilizumab Method. A retrospective cohort study of Brixia score, with clinical laboratory results of D-dimer, fibrinogen, ferritin, and CRP (C-reactive protein) COVID-19 patients with severe-critical phase who were administered standard therapy and tocilizumab who were treated at RSUP DR Kariadi Semarang, then a correlation was carried out between the Brixia score and clinical laboratory results using a correlation test Spearman. Results. The research data consisted of 72 subjects divided into groups that were adiminstered tocilizumab therapy (36 subjects) and standard therapy (36 subjects). There was a significant correlation between the Brixia score and the D-dimer result with p = 0.024 (p <0.05), correlation coefficient = 0.377 in the standard pre-therapy and post therapy. A p-value of less than 0.05 indicates no significant correlation between the Brixia score and clinical laboratory results before or after tocilizumab therapy. Conclusion. There is a significant correlation between the Brixia score results and the D-dimer results in COVID-19 patients who are adiministered standard therapy, but not significant correlation in tocilizumab